Saliva microbiome in primary Sjögren's syndrome reveals distinct set of disease‐associated microbes. (10th January 2020) - Sharma, Disha; Sandhya, Pulukool; Vellarikkal, Shamsudheen Karuthedath; Surin, Ajit Kumar; Jayarajan, Rijith; Verma, Ankit; Kumar, Anoop; Ravi, Rowmika; Danda, Debashish; Sivasubbu, Sridhar; Scaria, Vinod
Abstract: Objective: This study systematically aims to evaluate the salivary microbiome in patients with primary Sjögren's syndrome (pSS) using 16S rRNA sequencing approach. Methods: DNA isolation and 16S rRNA sequencing was performed on saliva of 37 pSS and 35 control (CC) samples on HiSeq 2500 platform. 16S rRNA sequence analysis was performed independently using two popular computational pipelines, QIIME and less operational taxonomic units scripts (LoTuS). Results: There were no significant changes in the alpha diversity between saliva of patients and controls. However, four genera including Bifidobacterium, Lactobacillus, Dialister and Leptotrichia were found to be differential between the two sets, and common between both QIIME and LoTuS analysis pipelines (Fold change of 2 and p  < .05). Bifidobacterium, Dialister and Lactobacillus were found to be enriched, while Leptotrichia was significantly depleted in pSS compared to the controls. Exploration of microbial diversity measures (Chao1, observed species and Shannon index) revealed a significant increase in the diversity in patients with renal tubular acidosis. An opposite trend was noted, with depletion of diversity in patients with steroids. Conclusion: Our analysis suggests that while no significant changes in the diversity of the salivary microbiome could be observed in Sjögren's syndrome compared to the controls, a set of four genera were significantly and consistently differential in the saliva of patients with pSS. Additionally, a difference in alpha diversity in patients with renal tubular acidosis and those on steroids was observed.